Information about others' choices selectively alters risk tolerance and medial prefrontal cortex activation across adolescence and young adulthood. (December 2021) - Braams, Barbara R.; Davidow, Juliet Y.; Somerville, Leah H.
Abstract: Adolescence is associated with major changes in the cognitive, emotional and social domains. One domain in which these processes intersect is decision-making. Previous research has shown that individuals' attitudes towards risk and ambiguity shape their decision-making, and information about others' choices can influence individuals' decisions. However, it is currently unknown how information about others' choices influences risk and ambiguity attitudes separately, and the degree to which others' choices shape decision-making differentially across development from adolescence to young adulthood. The current study used a computational modeling framework to test how information about others' choices influences these attitudes. Participants, aged 14–22 years, made a series of risky and ambiguous choices while undergoing fMRI scanning. On some trials, they viewed risky or safe choices of others. Results showed that participants aligned their choices toward the choice preferences of others. Moreover, the tendency to align choices was expressed in changes in risk attitude, but not ambiguity attitude. The change in risk attitude was positively related to neural activation in the medial prefrontal cortex. Results did not show age related differences in behavior and corresponding neural activation, indicating that the manner in which adolescents are influenced by peers is not ubiquitous but rather, is highly context-dependent.